An audit of hysterectomies at a tertiary care teaching hospital - Rajora, Parveen; Bhatti, Seema Grover (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hysterectomy is the second most common major surgical procedure performed on women all over the world next to caesarean section. Emergence of effective medical and conservative treatment for benign conditions in the uterus is now posing a question mark regarding the justification of hysterectomy. It has been realized that uterus should not be considered as a vestigial organ after child bearing. Apart from few population based studies, there is no national level survey done in India which give us the prevalence and indications for hysterectomy in India. Methods: Present study involved all patients who underwent Hysterectomy at Guru Gobind Singh Medical College Faridkot in a span of one year from 1st January 2017 to 31st December 2017. Results: In the year 2017, 250 hysterectomies were done, most common age group was 40-49 years (36.8%) and most common indication was fibroid uterus (40%) followed by ca ovary (19.6%), Abdominal route was most commonly preferred. Conclusions: Hysterectomy was justified in 98% women in our series based on post operative histopathological report of the specimen. However we hypothesize that 20 cases of DUB, 5 cases of CIN and 10 cases of endometriosis and 3 cases of chronic cervicitis could have been managed conservatively. 10 cases of obstetric hysterectomies could have been avoided by disseminating awareness among peripheral centres for early referral and by attempting a rather conservative approach of uterine artery embolizations. As the incidence of carcinoma is increasing in the Malwa region of Punjab people prefer hysterectomies instead of conservative treatment. Hysterectomy is used commonly to improve the quality of life and sometime it is life saving procedure. However it should be justified before taking a direct decision of sacrificing uterus.